The Impact of Covid-19 on McDonald’s Business: A Case Study of Malaysia - Kee, Daisy Mui Hung; Toh, Aik Long; Chong, Jin Hui; Teng, You Ming; Ooi, Shawn Jinq Cheng; Chong, Rachel Xin Jie (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2021)
The purpose of the study is to identify the impacts of Covid-19 on McDonald’s business in Malaysia. McDonald’s is one of the largest fast-food franchises, and its franchisee is expanding yearly in the global market. Its mission is to become the favorite place and way to eat and drink. A total of 100 respondents were surveyed. Results indicated that the Covid-19 has an impact on its business performance. The impacts are the drop in sales, an increase in operational costs as well as changes in their operation.